Biophysical and hydrological changes in soils under livestock grazing varying slopes in the East African highlands - Mwendera, E.J.; Mohamed-Saleem, M.A. (International Grassland Society, 1997)
The impacts of grazing on biophysical and hydrological properties of grazing lands were investigated on two sites represting 0-4 percent and 4-8 percent slopes at the Livestock research Institute (ILRI) Debre Zeit research station, 50 km South of Addis Ababa. Grazing pressure differently influence ground vegetative cover, increased surface runoff and soil loss, and reduced water infiltrability of the soil between the two land slopes. Grazing management strategies need to be `slope-specific' and more research is needed to quantify biophysical changes in order to asses cumulative long term effects of grazing and trampling on vegetation, soil, and hydrology of grazing lands and complement efforts that seek to cohesively and compatibly manage land resources to sustainably serve multiple needs of communities.